Bioengineered cell culture systems of central nervous system injury and disease. Issue 9 (September 2016) - Teixeira, Fábio G.; Vasconcelos, Natália L.; Gomes, Eduardo D.; Marques, Fernanda; Sousa, João C.; Sousa, Nuno; Silva, Nuno A.; Assunção-Silva, Rita; Lima, Rui; Salgado, António J.
Highlights: 3D cell culture models are needed in as current 2D models do not recapitulate the CNS niche. Combinatory strategies using cells, hydrogels and microfluidics chambers allow to develop 3D cell culture models. The development of 3D cell culture models will provide the tools for future models that recapitulate the degenerative or injured CNS. Abstract : Cell culture systems, either 2D or explant based, have been pivotal to better understand the pathophysiology of several central nervous system (CNS) disorders. Recently, bioengineered cell culture systems have been proposed as an alternative to the traditional setups. These innovative systems often combine different cell populations in 3D environments that more closely recapitulate the different niches that exist within the developing or adult CNS. Given the importance of such systems for the future of CNS-related research, we discuss here the most recent advances in the field, particularly those dealing with neurodegeneration, neurodevelopmental disorders, and trauma.